2009
DOI: 10.1016/j.neuroscience.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parkinson's disease on proprioceptive control of posture and reaching while standing

Abstract: Although previous studies have shown pointing errors and abnormal multijoint coordination in seated subjects with PD who cannot view their arm, the extent to which subjects with PD have problems using proprioception to coordinate equilibrium maintenance and goal-oriented task execution has not been adequately investigated. If a common motor program controls voluntary arm pointing movements and the accompanying postural adjustments, then impairments of proprioceptive integration in subjects with PD should have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 54 publications
2
41
2
2
Order By: Relevance
“…Individuals with PD do not promptly adjust the magnitude of their postural responses based on their initial posture (Horak et al 1999;Rocchi et al 2006), direction of perturbation (Chong et al 1999a), instructional set (Chong et al 1999a(Chong et al , 1999b(Chong et al , 2000, or prior experience (Chong et al 1999a(Chong et al , 2000De Nunzio et al 2007). Of particular interest for the present study, individuals with PD have been found to be impaired at integrating control of postural stability with the goal of voluntary tasks such as step initiation (Burleigh-Jacobs et al 1997;Gantchev et al 1996;Rocchi et al 2006), trunk bending (Alexandrov et al 1998), and pointing to a target (Tagliabue et al 2009). Tagliabue et al (2009) showed that as the stability constraint imposed by a pointing task increases, functional integration between the voluntary and postural tasks decreases in individuals with PD.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Individuals with PD do not promptly adjust the magnitude of their postural responses based on their initial posture (Horak et al 1999;Rocchi et al 2006), direction of perturbation (Chong et al 1999a), instructional set (Chong et al 1999a(Chong et al , 1999b(Chong et al , 2000, or prior experience (Chong et al 1999a(Chong et al , 2000De Nunzio et al 2007). Of particular interest for the present study, individuals with PD have been found to be impaired at integrating control of postural stability with the goal of voluntary tasks such as step initiation (Burleigh-Jacobs et al 1997;Gantchev et al 1996;Rocchi et al 2006), trunk bending (Alexandrov et al 1998), and pointing to a target (Tagliabue et al 2009). Tagliabue et al (2009) showed that as the stability constraint imposed by a pointing task increases, functional integration between the voluntary and postural tasks decreases in individuals with PD.…”
mentioning
confidence: 90%
“…Of particular interest for the present study, individuals with PD have been found to be impaired at integrating control of postural stability with the goal of voluntary tasks such as step initiation (Burleigh-Jacobs et al 1997;Gantchev et al 1996;Rocchi et al 2006), trunk bending (Alexandrov et al 1998), and pointing to a target (Tagliabue et al 2009). Tagliabue et al (2009) showed that as the stability constraint imposed by a pointing task increases, functional integration between the voluntary and postural tasks decreases in individuals with PD. The high stability constraint condition led to poorer control of the center of body mass (CoM) in subjects with PD, whereas performance on the voluntary task was unaffected (Tagliabue et al 2009).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This result was similar our study. It was indicated good posture was closely related performing functional movement 21,22) . Parkinson's disease patients performing a balance of visual surround and low-extremity strength training programs improved their equilibrium and strength.…”
Section: Discussionmentioning
confidence: 98%
“…As previously reported by many authors, organization protocols are useful for the assessment of postural control under various sensory conditions and generally accepted as a reliable paradigm of measuring the capacity of the central nervous system to prioritize and reintegrate sensory information. 32,43 Tagliabue et al 40 reported that these patients showed a breakdown in the temporal coordination between postural adjustments and arm reaching during whole body reaching to a target when closing their eyes. Abnormal postural coordination when vision was obscured is consistent with impaired proprioceptive mapping compensated by the use of vision.…”
Section: Balance Assessmentmentioning
confidence: 99%